O discurso intolerante contra a mulher nas redes sociais : uma análise bakhtiniana - Martins, Luciane Alves Branco (2020)
The presente work aims to analyze the construction of intolerant discourse against women on social networks. With the internet, intolerance, which already existed, has spread, with women being a constant target of insults. In the theoretical framework of this research, concepts developed by the Bakhtin Circle are presented that support the dialogical perspective of the discourse. The reflection on the concepts of intolerance and intolerant discourses are based on the ideas of Diana Barros, Roger-Pol Droit and Ruth Amossy. A study on feminism was also developed, based on the conception of Simone de Beauvoir and Michelle Perrot. As for the methodological procedures, a survey was carried out on three social networks, namely Facebook, Twitter and Instagram, to survey these speeches, considering that, in the materialization of messages, there is the spread of speeches that disqualify women. In order to limit the collection on these social networks, the terms "machismo" and "machista" were used due to the numerous posts of a macho nature, which defend their position. From this delimitation, about 70 Brazilian communities were found on Facebook; on Twitter, about 30 Brazilian profiles, and on Instagram, around 40 Brazilian profiles were found. The collection was carried out in posts published in the period between January 2014 and August 2019 on the referred social networks and for the selection of material, the following criteria were considered: a) search on social networks for the terms “machismo” and “machista” in Brazilian communities or profiles; b) posts whose theme was to disqualify women from the use of derogatory tones to their image. Due to the analysis of the social media posts Facebook, Twitter and Instagram chosen for this research, it is understood that the image of women that circulates in the social networks analyzed is that whose main function is being a housewife, mother and wife, and that he must remain in his home, otherwise he would be in danger outside the home. This woman also has her individuality underestimated, since only after cleaning the house can she think about her personal projects. In addition, there is the tension of a football professional, who would not (for the speaker) have the aptitude to perform this function. The three posts show that there is still a long way to go before a woman can decide about her life, with the respect she deserves.